Kepastian Hukum dalam Penyelesaian Sengketa Agraria: Reformasi Eksekusi Putusan yang Berkeadilan - Abisha, Dziqry Irga; Surahman, Surahman; Yulianingrum, Aullia Vivi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Agrarian conflicts in Indonesia, particularly those occurring in East Kalimantan, reflect a profound weakness in the system of fair and effective dispute resolution. Although court rulings have obtained permanent legal force—as exemplified by Decision No. 3/Pdt. Eks/2023/PN. Trg—the execution of such rulings still faces significant obstacles. This study aims to identify the causes behind the failure of agrarian dispute executions and to propose a model for more just and effective resolution. Adopting the perspective of Thomas Aquinas’s theory of justice, this research emphasizes three core principles of justice in resolving agrarian disputes: distributive justice, legal justice, and commutative justice. Based on these principles, the article proposes a set of strategic solutions to enhance the effectiveness of agrarian dispute settlements. These include strengthening mediation before execution, reconstructing execution regulations to limit baseless objections, harmonizing land data to prevent overlapping certificates, and applying a social approach to execution that considers the welfare of affected communities. This study is expected to contribute to the reform of agrarian dispute resolution regulations in Indonesia, with the ultimate goal of establishing a more efficient, equitable, and sustainable system.